Programming Language Concepts and Paradigms - Findlay William; Hughes John; Watt David A (Prentice Hall, 1990)
This book provides an introduction to the concepts underlying programming languages and the major language paradigms. Preface, Introduction, Values, Storage, Bindings, Abstraction, Encapsulation, Type Systems, Sequencers, Concurrency by William Findlay, The Imperative Programming Paradigm, The Concurrent Programming Paradigm, The Object-Oriented Programming Paradigm, The Functional Programming Paradigm, The Logic Programming Paradigm, Conclusion, Bibliography, Index.